2000
DOI: 10.1002/1099-0682(200012)2000:12<2459::aid-ejic2459>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-Assisted Condensation of 2-Butanone Oxime and Acetone: Synthesis and X-ray Structure of the Novel Acetaldiimine Complex [CoI2{((CH3CH2)(CH3)C=NO)2C(CH3)2}]

Abstract: The synthesis of the first acetaldiimine cobalt complex and its full characterisation are reported. The nitrogen‐bonded chelate complex [CoI2{((CH3CH2)(CH3)C=NO)2C(CH3)2}] is obtained in high yield from the reaction of 2‐butanone oxime with cobalt iodide dihydrate in acetone, in the presence of trimethyl orthoformate as dehydrating agent. A single‐crystal X‐ray structure determination, infrared spectroscopy and mass spectrometry analyses confirm the formation of a new ligand in situ from the addition of an ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
0
11
0
1
Order By: Relevance
“…We will now address the connectivity pattern sketched in Scheme 5a, with different coordination polyhedra along the chains. Sequences of alternating octahedral and tetrahedral Co(II) sites have been described by Bouwman et al [10] for two closely related but not isomorphous chain polymers. A comparable sequence of octahedrally and tetrahedrally coordinated Cd(II) cations has been found in [Cd(-I) 2 Cd(-I) 2 (dmso) 2 ] [170].…”
Section: Chains Incorporating Unsubstituted Metal-halide Fragmentsmentioning
confidence: 83%
See 1 more Smart Citation
“…We will now address the connectivity pattern sketched in Scheme 5a, with different coordination polyhedra along the chains. Sequences of alternating octahedral and tetrahedral Co(II) sites have been described by Bouwman et al [10] for two closely related but not isomorphous chain polymers. A comparable sequence of octahedrally and tetrahedrally coordinated Cd(II) cations has been found in [Cd(-I) 2 Cd(-I) 2 (dmso) 2 ] [170].…”
Section: Chains Incorporating Unsubstituted Metal-halide Fragmentsmentioning
confidence: 83%
“…Crystallization has often been challenging, for us as well as for other groups. Several authors reported problems with crystallization [6][7][8][9][10]. Consequently, structure determination based on powder data is relatively frequent among the compounds discussed in this contribution [9,[11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 98%
“…As an example, Hitchcock and co-workers described the synthesis of a polymeric heterometallic aggregate formed by reaction between FeCl 2 and CoCl 2 in THF, followed by recrystallization from ethanol-containing CHCl 3 (Hitchcock et al, 2003). Also, Hierso and co-workers reported the dehydration of CoCl 2 Á6H 2 O with trimethyl orthoformate in THF solution, generating a polymeric complex in which the presence of both thf and methanol as ligands imparts a different coordination environment to the cobalt(II) centres when compared to that in (2 0 ) (Hierso et al, 2000).…”
Section: Figurementioning
confidence: 99%
“…21 Tetrahedral Co(II) sites are coordinated only by chlorides, while O-donor ligands and bridging chlorides are coordinated to octahedral Co(II) sites in the complexes 2, [Co 4 (-Cl) 6 Cl 2 (thf) 4 21 and [Co 4 (-Cl) 6 Cl 2 (thf) 4 (MeOH) 2 ] n (2.251(3) Å). 32 The interatomic CoCl (bridging) distances in the polymeric complex 2 are in a wide range from 2.266(1) to 2.500(1) Å (Table 3) due to connections of different polyhedra by single and double chloride bridges. A similar variety of interatomic CoCl (bridging) distances was found in polymeric complexes [Co 4 (-Cl) 6 Cl 2 (thf) 4 (MeOH) 2 ] n (2.2861(7) 2.5488(7) Å) 32 and [Co(daa) 2 (-Cl) 2 CoCl 2 ] n (2.295(2) 2.455(2) Å).…”
Section: Crystal Structure Of the Polymeric Complex 1 2 Andmentioning
confidence: 99%
“…32 The interatomic CoCl (bridging) distances in the polymeric complex 2 are in a wide range from 2.266(1) to 2.500(1) Å (Table 3) due to connections of different polyhedra by single and double chloride bridges. A similar variety of interatomic CoCl (bridging) distances was found in polymeric complexes [Co 4 (-Cl) 6 Cl 2 (thf) 4 (MeOH) 2 ] n (2.2861(7) 2.5488(7) Å) 32 and [Co(daa) 2 (-Cl) 2 CoCl 2 ] n (2.295(2) 2.455(2) Å). 21 The average CoCl (bridging) distances in the dinuclear complexes 1 and 3 are in the same range; approximately 2.32 Å to tetrahedral Co2 and 2.44 Å to octahedral Co1.…”
Section: Crystal Structure Of the Polymeric Complex 1 2 Andmentioning
confidence: 99%